IMPLEMENTASI BIMBINGAN KELOMPOK DENGAN TEKNIK DISKUSI KELOMPOK DALAM MENINGKATKAN KECERDASAN EMOSIONAL PESERTA DIDIK DI SEKOLAH DASAR - Aisyah Nurul Izzah; Sumantri, Syarif; Dallion, Engga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Emotional intelligence is important for the social and academic development of elementary school students, but there are still students who lack empathy and self-confidence. This study aims to determine how group guidance with group discussion techniques can improve students' emotional intelligence. The study was conducted qualitatively with a descriptive approach at SDN Rawamangun 05 East Jakarta, with the subjects being homeroom teachers and class V C students. Data were collected through observation, interviews, documentation, and literature studies. The results of the study showed an increase in the aspects of empathy, cooperation, emotional control, and self-confidence of students after participating in group discussion activities. The conclusion shows that group guidance with group discussion techniques is successful in improving the emotional intelligence of elementary school students. However, it is necessary to develop variations in methods in group discussions to increase the sustainability of the program's impact.